Vocational Consulting and Guidance in Contemporary Vocational Training Context - Barkauskaitė, Marija (Acta Paedagogica Vilnensia, 2007)
The subject of this paper is vocational consulting and guidance in contemporary vocational training context. As Lithuania is integrating into the European social and economic space, vocational consulting has become an under-flying field which helps people to realize vocational perfection’s solutions. This paper was aiming to study the evolution of vocational training system in the last ten years establishing the importance of vocational consulting and guidance for planning of professional career. The object of research was pedagogical process in vocational training. It was hypothesized: analysis of regional state demonstrates that it is possible to bargain for qualitative vocational training if it develops purposefully the partnership of comprehensive schools with stakeholders, the relations of territorial labour markets with the institutions of vocational training, if it evaluates vocations of students, their interests, abilities and relevance of the choice of profession and if it strengthens and perfects attributions of vocational teacher. There was applied the empirical quantitative evaluation in this research. The data was obtained executing written questionnaires and applying the method of sources and documentation. Afore-mentioned problems have determined the purpose of the research - to deal with the development of vocational training system in Lithuania by revealing the importance of vocational orientation and counselling in the process of vocational training. The object of the research is teaching process in the vocational training. Considering the strategic national and educational goals to integrate into the social and economic space of European Union, vocational counselling becomes a priority. Systemically implemented researches by observing quality of education and qualification allow us to assume that vocational orientation and counselling raises particular requirements to each profession.